Bibliometric Analysis Using VOSviewers with Publish or Perish of “Academic Reading” - Pujiastuti, Indah (ASEAN Journal of Educational Research and Technology, 2024)
The purpose of this study is to present an overview of the development of research on academic reading. Data were obtained from POP with Google Scholar database from 2014-2024. A total of 776 articles were examined. We evaluated this database using Vosviewer analysis and categorized the articles. The results show that the development of research related to academic reading has fluctuated over the last 10 years. From hundreds to tens and in 2023 and 2024 the number of articles is only in the single digits.  The most cited article was in 2014 with 330 citations.  Four clusters were found. Ten items make up cluster 1 (academic article, academic reading, academic reading comprehension, academic reading skill, development, metacognitive reading strategy, metacognitive strategy, paper, and reading strategy). Cluster 2 with 8 items (academic achievement, academic performance, academic success, habit, impact, performance, reading habit, relationship). Cluster 3 with 5 items (comprehension, effectiveness, narrative text, reading comprehension, and recount text), and five items make up cluster 4 (academic purpose, academic text, article, practice, and university).  We believe that this way will be more effective in summarizing various research results related to academic reading and will be useful in presenting comprehensive facts as an initial basis for conducting similar research.